BIJAK MENGGUNAKAN INTERNET DI PANTI ASUHAN AISYIYAH PADANG - Sri Restu Ningsih; Ade Irma Suryani; Rahmadini Darwas; Rahimulaily Rahimulaily; Arman Arman (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The COVID-19 pandemic has had a huge impact on society, especially in the education sector. Where students are required to study online. This makes it difficult for students, because of the lack of knowledge of students using the internet in the learning process. The purpose of this Community Service (PKM) is to provide increased knowledge about how to use the internet wisely, in its use as an online learning medium during online learning for Aisyiyah Padang Orphanage students. For this reason, it is necessary to train students how to use the internet wisely. The method used in this PKM is in the form of lectures, training and questions and answers about using the internet effectively. The material provided is in the form of training on how to use the internet wisely during online learning. The results of this PKM activity provide many benefits and technological knowledge for students, because so far students do not get the knowledge about technology that they get from school.